Going Strong: The Role of Physical Strength among the Scots of Eastern Nova Scotia and Cape Breton - Stanley-Blackwell, Laura; MacDonald, Shamus (Material Culture Review)

(untitled) (Cape Breton University Press, 2015)
Abstract Drawing on the disciplines of social history and folklore, this article examines a much-neglected dimension of local story lore—feats of strength stories—among the immigrant Scots and their descendants in Eastern Nova Scotia and Cape Breton. Fieldwork conducted in both Gaelic and English, as well as print sources, document the rich prevalence of stories about exceptional physical strength and stamina, which once served as vital expressions of identity and community. These stories still form a vigorous component of the regional folktale corpus and represent a favourite genre among tradition bearers.